2023
DOI: 10.1002/advs.202301854
|View full text |Cite
|
Sign up to set email alerts
|

MnO2 Nanoflower Integrated Optoelectronic Biointerfaces for Photostimulation of Neurons

Lokman Kaya,
Onuralp Karatum,
Rıdvan Balamur
et al.

Abstract: Optoelectronic biointerfaces have gained significant interest for wireless and electrical control of neurons. Three–dimentional (3D) pseudocapacitive nanomaterials with large surface areas and interconnected porous structures have great potential for optoelectronic biointerfaces that can fulfill the requirement of high electrode‐electrolyte capacitance to effectively transduce light into stimulating ionic currents. In this study, the integration of 3D manganese dioxide (MnO2) nanoflowers into flexible optoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Since in our previous studies we demonstrated that the use of P3HT on the biointerface had no adverse effect on cell survival, , at first we tested the effect of AgBiS 2 NCs on primary hippocampal cells by using devices without the P3HT layer. Morphological features of neurons during the 14-day culture period were maintained on ITO/ZnO/AgBiS 2 devices and showed no significant alteration in morphology with respect to the control group (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…Since in our previous studies we demonstrated that the use of P3HT on the biointerface had no adverse effect on cell survival, , at first we tested the effect of AgBiS 2 NCs on primary hippocampal cells by using devices without the P3HT layer. Morphological features of neurons during the 14-day culture period were maintained on ITO/ZnO/AgBiS 2 devices and showed no significant alteration in morphology with respect to the control group (Figure S9).…”
Section: Resultsmentioning
confidence: 99%